ASSOCIATION OF SERUM CHLORIDE LEVEL WITH HYPERTENSION. - Kumari, Dr. Ruby; Lal, Dr. Lakshman (Student’s Journal of Health Research Africa, 2023)
Background: The most abundant anion in our body, along with sodium, is chloride (Cl), which is primarily obtained through dietary sources. Studies indicate that greater dietary Chloride intake raises blood pressure, and higher serum Cl seems to be linked to decreased cardiovascular risk and death. This indicates that serum Chloride reflects risk pathways independent of blood pressure, serum sodium, and serum bicarbonate. It is uncertain how serum chloride affects a patient’s long-term survival after developing pulmonary arterial hypertension. Methods: This study included patients with hypertension, idiopathic or heritable, who had a basic metabolic panel when they were diagnosed with hypertension. Results: Over time, serum chloride had no obvious impact on systolic blood pressure. Only serum bicarbonate among electrolytes demonstrated an independent impact on longitudinal blood pressure. Conclusion: This study has shown the association of chloride with systolic and diastolic blood pressure. Recommendation: More studies are now needed to elucidate the mechanisms of the association between low serum Chloride levels and mortality outcomes if more studies confirm and extend our findings. Our findings may be applied in clinical practice to recognize persons with high-risk hypertension as Chloride measurement is a critical component of routine clinical screening.